The Efforts of the Turjawali Unit of the Samapta Unit in Preventing the Crime of Motorized Vehicle Theft in the Jurisdiction of the Kediri City Police Station - Kurniawan, Alif Dhuhriadi (Police Studies Review, 2024)
This article is motivated by the increasing criminal offence of theft of motorised vehicles in Kediri City from year to year. Therefore, this study aims to analyse and describe what factors influence and how the efforts of the unit turjawali unit samapta in Kediri City Police in preventing criminal acts of theft of motor vehicles and know the efforts used by the author in analysing these efforts through POAC management theory and its management elements (man, money, method, materials). Then for the concept used the concept of crime prevention and patrol. Furthermore, this research was conducted with a qualitative approach and used the type of field research. The results of this study are the efforts of the turjawali unit in preventing criminal acts of theft of motorised vehicles through patrol activities carried out using Perkabaharkam No. 1 of 2017 concerning patrols. The results of the research found by the author are the factors that influence the turjawali unit in preventing criminal acts of theft of motorised vehicles from human resources, finance, methods, and facilities and infrastructure. Then how the efforts made by the turjawali unit in preventing criminal acts of motor vehicle theft are through patrol activities carried out starting from planning, then organising through a picket schedule, then implementing and how to control it. For the conclusion that can be drawn that the number of members in the Kediri City Police turjawali unit is still not in accordance with the DSP stipulated in the Regulation of the Indonesian National Police No. 2 of 2021. Then. Then the efforts made by the turjawali unit in preventing criminal acts of theft of motorised vehicles are still not in accordance with what was planned and organised. The implementation of patrols in terms of following the route is still not appropriate and the picket schedule is still not followed properly. Then the advice given by the author is that HR empowerment should be adjusted to Perpol No. 2 of 2021 Then in the implementation of patrols to follow Perkabaharkam No. 1 of 2017 and follow the plans, schedules, and routes that have been prepared and determined so that the prevention of criminal acts of motor vehicle theft can run well.